Characterization of Titanium Alloy Ti-6Al-4V Fabricated Using Friction Stir Additive Manufacturing - Ahmed, Assem Mohamed Abdelaziz (2025)
A Master of Science thesis in Mechanical Engineering by Assem Mohamed Abdelaziz Ahmed entitled, “Characterization of Titanium Alloy Ti-6Al-4V Fabricated Using Friction Stir Additive Manufacturing”, submitted in Fall 2025. Thesis advisors are Dr. Maen Alkhader and Dr. Basil Darras. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).